Tinjauan Etika Anti-Kekerasan Terhadap Peran Orang Tua Dalam mendidik Remaja 15-17 Tahun Di GMIT Emaus Liliba - Mboro, Whilly Mesakh; Ludji, Irene; Lusi, Astrid Bonik (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2024)
Non-violence ethics wants to invite parents to play their duties and roles as non-violence ethics educators. This research was carried out using qualitative methods with a narrative-descriptive approach. It is hoped that through a narrative-descriptive approach, the context can be investigated to see how the role of parents becomes educators. At GMIT Emmaus Liliba, cases of violence against children are pretty high, and, unfortunately, violence is carried out by those closest to them, such as parents and other family members. Most parents at GMIT Emmaus Liliba understand that a child needs to be educated with full attention and affection in adolescence. However, for them, violence is also necessary if the child is disobedient. Robert L. Holmes believes that awareness, consistency, and never giving up are the first steps in parents' efforts to present new, creative, non-violent educational patterns. Therefore, non-violence education is the path that needs to be chosen so that the implementation of education in the family improves the lives of teenagers aged 15-17.